Post-tonsillectomy pain control: consensus or controversy?. (January 2016) - Cohen, Natasha; Sommer, Doron D
Pediatric post-tonsillectomy analgesia continues to be highly debated and an area of active research. Tonsillectomy pain can lead to significant patient morbidity, and incur potentially avoidable healthcare costs. Moreover, the various analgesic classes, each present their own risk profiles and unique side effects when used in children post-tonsillectomy. This review delineates the clinical and pathophysiological basis for post-tonsillectomy pain, types of analgesics and their risk profiles, as well as special considerations in this clinical population and a review of alternative analgesic treatment options. This article presents a summary of recent literature and discusses evidence-based management options to aid medical and allied health professionals who may encounter these patients.